Analisis Merger Pada PT Indosat Tbk (ISAT) Terhadap PT Hutchison 3 Indonesia (H3I) - Adi Putra Pratama; Abrar Rizqi Destriawan; Endang Kartini Panggiarti (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze the impact of the merger between PT Indosat Tbk (ISAT) and PT Hutchison 3 Indonesia (H3I) on both companies. Through a merger analysis approach, we identify key factors that influence the success or failure of the integration between these two entities. The research method is literature review to search a financial information and annual reports. Qualitative and quantitative analyses are used to measure the impact of the merger on the financial, operational, and reputational performance of both companies. The research findings indicate that the merger between ISAT and H3I has a positive impact on operational efficiency and economies of scale. However, challenges related to technology integration, corporate culture, and human resource management are also identified as critical factors that need to be addressed. Furthermore, this research discusses the implications of the merger on the telecommunications market in Indonesia and its impact on industry competition. These findings provide valuable insights for business practitioners, regulators, and academics interested in the study of merger impacts in the telecommunications sector.